Die Rosenkreuzer als imaginäre Gesellschaft - Ralph Häfner (Recherches Germaniques)
Wilhelm Hoßbach (1784-1846) was a preacher at the cadets’ house in Berlin. Intellectually close to Friedrich Schleiermacher he aimed at reconciling religiousness and science within the spirit of the mediation theology of his time. The reasons for the increasing interest in Johann Valentin Andreae’s character and work since the end of the 18th century have to be understood in the context of multiple motivations. Through his Rosicrucian writings—more precisely the Fama fraternitatis and the Chymical Wedding—Andreae’s work has provided throughout history starting points for the Masonic movement, who was sometimes thought to have originated in the secret Rosicrucian society. Hoßbach however places Andreae’s Chymical Wedding in the context of the critical and satirical writings towards the controversial author directed against his time and society. He is convinced that Andreae’s work is an early novel, which had already been circulated as a manuscript twelve years before the publication of the Fama. He suggests that the Lutheran orthodoxy (Hoßbach quotes Christian Gilbert de Spaignart, Valentin Griesmann, Georg Rost and Nicolaus Hunnius) ignored the satirical nature of the novel aiming its attack against a society that didn’t exist. Andreae’s novel could then be read rather as “a game with the bizarreness of his time that must have depicted the foolishness of rubbernecks, a mockery of all these whimsical phenomena which abounded in the century, of scholars and bigheaded fools, especially of Paracelsians, alchemists and dreamers of all kinds. It is a novel full of sweet and delightful literature, of delicate satirical lines but also of the strangest fantasies in the fashion of his time”.